Contemporary art, photography, and the politics of citizenship - Maimon, Vered (New York, NY : Routledge, 2020)
"This book analyzes recent artistic and activist projects in order to conceptualize the new roles and goals of a critical theory and practice of art and photography. Vered Maimon argues that current artistic and activist practices are no longer concerned with the "politics of representation" and the critique of the spectacle, but with a "politics of rights" and the performative formation of shared yet highly contested public domains. The book thus offers a critical framework in which to rethink the artistic, the activist, and the political under globalization. The primary focus is on the ways contemporary artists and activists examine political citizenship as a paradox where subjects are struggling to acquire rights whose formulation rests on attributes they allegedly don't have; while the universal political validity of these rights presupposes precisely the abstraction of every form of difference, rights for all. The book will be of interest to scholars working in art history, contemporary art, photography theory, visual culture, cultural studies, critical theory, political theory, human rights, and activism"--
OCLC-licensed vendor bibliographic record.
Keywords: Aesthetics -- Political aspects; Art -- Philosophy; Photography -- Philosophy; Critical theory; PHOTOGRAPHY / History